On the Late Stage of the Point Explosion in an Exponential Medium and Self-Similar Raizer’s and Hayes’s Solutions - Markov, A.A. (Engineering Transactions, 1974)
The influence of the effects of counter pressure, gravity force and initial conditions on the asymptotic of the solution in upper region of the flow and under one is investigated. t is shown that calculation of gas-dynamics of the late stage of the explosion (stage of acceleration of upper part of a shock) require the estimation of the interaction of upper and lower regions of the flow. The conjugation conditions of both regions arc suggested and some examples of calculations for the plane shock are presented.